Floating double probe characteristics of non-thermal plasmas in the presence of zeolite - Liu, Chang-jun; Wang, Jia-xin; Yu, Kai-lu; Eliasson, Baldur; Xia, Qing; Xue, Bingzhang; Zhang, Yu-hang (Journal of electrostatics, 2002)
The combination of catalyst and non-thermal plasmas has led to some unusual chemical behaviors, especially with zeolite catalyst. A mechanism has been proposed to explain the observed interaction between catalyst and non-thermal plasmas. This mechanism includes two aspects: plasma promoted or induced catalysis and catalyst enhanced non-equilibrium of non-thermal plasmas. In this paper, we present some direct experimental evidence for the catalyst (zeolite)-enhanced non-equilibrium of non-thermal plasmas suggesting the use of zeolite increases, significantly, the electron temperature of non-thermal plasmas, while the gas temperature remains unchanged. A floating double-probe characteristic has been utilized to measure the electron temperature. Compared to the case without zeolite, the electron temperature of non-thermal plasmas with Mo-Zn/HZSM-5 increases up to 250%, while, at the same time, the discharge power reduces 58%, compared to that without zeolite.